Factors Contributing to Uterine Scar Dehiscence in Pregnant Women with Previous One Caesarean Section at Al-Elwiya Maternity Teaching Hospital - Abdulameer, Dania Isam; Sarsam, Samar Dawood (Journal of Science in Medicine and Life, 2025)
Background: Uterine scar dehiscence is considered an incomplete division of the three layers of the uterus: the perimetrium, myometrium and endometrium, allowing visibility of the fetus through the perimetrium. The reported incidence of the cesarean section scar dehiscence ranges from 0.2% to 4.3%. Previous cesarean section scar dehiscence is a well-known risk factor for uterine rupture during trial of labor in subsequent pregnancy. An appropriate screening method for such cases and the best surgical approach for repairing scar dehiscence during delivery does not exist or has not been established. Aim of the study: To estimate the incidence and risk factors for cesarean section scar dehiscence in pregnant women with previous one cesarean section scar who undergo second cesarean section delivery at Al-Elwiya Maternity Teaching hospital. Patients and methods: This is a cohort study conducted in the Department of Obstetrics and Gynecology at Al-Elwiya Maternity Teaching Hospital / Baghdad during a period extending from the 1st of January 2022 till the 1st of October 2022. The study included all pregnant women with a viable fetus and a history of previous one cesarean section who became a candidates for cesarean section delivery. Follow-up of the cases was done to estimate the risk factors, presentation, maternal and neonatal outcomes. Results: The study included 727 women who had a history of previous cesarean section and according to the status of the uterus, they were divided into two groups, first group those with scar dehiscence were 177 cases (24.3%) and the second group without dehiscence were 550 cases. The mean maternal age, body mass index, and parity were not different between the two groups. The current pregnancy gestational age was not different between the two groups, on the contrary, the mean gestational age of previous pregnancy was significantly lower in the first group. Regarding the interpregnancy interval, the first group had a significantly shorter interpregnancy interval less than 2 years. Pregnants who had their previous cesarean section in a private hospital had significantly higher dehiscent scar. The presentation was statistically different between the two groups, the scar tenderness, uterine contraction and bleeding were significantly higher in the first group, while the rate of active labor was significantly lower in the fisrt group compared to those in the second group. Regarding intraoperative findings cases with upper uterine segment scar were significantly higher in the first group than those in the second group. Regarding maternal outcome there was no difference in the rate of morbidity or mortality between the two groups, also neonatal outcome, no difference was found in Apgar score or birthweight between the two groups. Conclusion: The incidence of uterine scar dehiscence in pregnants with previous one cesarean was 24.3%. Previous delivery before 37 weeks of gestation, shorter interpregnancy interval less than 24 months, upper segment uterine scar and delivery in a private hospital were the most common risk factors for uterine scar dehiscence. Scar tenderness, vaginal bleeding, uterine contractions and failure to achieve active labor were the most common presentation of uterine scar dehiscence.